Making the Eurozone work: A risk-sharing reform of the European Stability Mechanism - Giovanni Dosi; Marcello Minenna; Andrea Roventini; Roberto Violi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
This work presents an original proposal for the reform of the Eurozone architecture according to an approach based on risk sharing (aiming to reach in the long-term the mutualization of public debt). The proposal envisages a new role for the European Stability Mechanism (ESM) which should gradually become the guarantor of the public debts of the EMU. In this way, the new ESM would support the full transition from national debts to a single Eurozone public debt (e.g. Eurobonds) with a single yield curve for all countries. Our proposal would benefit both core and peripheral EMU countries. Indeed, the riskiest countries, which would gain from the ESM conditional debt guarantee, should give up the possibility of redenominating their national debt and would pay to the ESM the corresponding market price of the guarantee. This would strengthen the capital endowment of the ESM and also allow it to use its leverage capability to support the realignment of the economic cycles of the different countries through profitable public investment plans concentrated in the weakest regions of the EMU. Such plans would be coordinated and implemented by the European Union. After a transition period, our Insurance Fund proposal would contribute to a much more resilient monetary union, with a European fiscal policy and debt. Admittedly this proposal presupposes a political consensus at the EU level to reinterpret to the no bailout rule enshrined in the treaties so that risk sharing institutions implemented with fairly priced insurance scheme can be allowed. New risk sharing institutions will foster a common vision of belonging to the same federal, political union in the making, the only one compatible with the abdication of fiscal sovereignty by national governments.
Keywords: E02; G01; H12; H63; 330; Sovereign Debt; Risk-Sharing; Insurance Fund; ESM; ECB; OMT; QE; CDS spread; Investments' Multiplier; Bond-Market Discipline; Safe Asset